A Hybrid FMCW-Interferometry Radar for Indoor Precise Positioning and Versatile Life Activity Monitoring - Guochao Wang; Changzhan Gu; Inoue, Takao; Changzhi Li (IEEE transactions on microwave theory and techniques, 2014)
This paper presents a hybrid radar system that incorporates a linear frequency-modulated continuous-wave (FMCW) mode and an interferometry mode for indoor human localization and life activity monitoring applications. The unique operating principle and signal processing method allow the radar to work at two different modes for different purposes. The FMCW mode is responsible for range detection while the interferometry mode is responsible for life activities (respiration, heart beat, body motion, and gesture) monitoring. Such cooperation is built on each mode's own strength. Beam scanning is employed to determine azimuth information, which enables the system to plot 360° 2-D maps on which the room layout and objects' location can be clearly identified. Additionally, the transmitted chirp signal is coherent in phase, which is very sensitive to physiological motion and allows the proposed technique to distinguish human from nearby stationary clutters even when the human subjects are sitting still. Hence, the proposed radar is able to continuously track the location of individuals and monitor their life activities regardless of the complex indoor environment. A series of experiments have been carried out to demonstrate the proposed versatile life activity monitoring system.